A Survey of Role-Based Access Control Implementation in HMI Systems for Industrial Automation - Alpeshkumar Kathiriya (International Journal of Advanced Control and System Engineering, 2025)
The convergence of Role-Based Access Control (RBAC) and Human-Machine Interface (HMI) systems presents a transformative approach to secure and efficient industrial automation in Industry 4.0. By integrating RBAC with Multi-Factor Authentication (MFA), this framework enhances cybersecurity while maintaining operational flexibility, mitigating both external threats and internal vulnerabilities. Modern adaptive HMIs further optimize user experience through personalized and intuitive interfaces, though challenges remain in balancing functionality with simplicity in complex industrial environments. Future research directions include AI-driven dynamic RBAC for real-time permission adjustments, blockchain-based decentralized access control, and quantum-resistant encryption for safeguarding SCADA systems. Additionally, advancements in behavioral biometrics, predictive HMIs, and explainable AI will refine security and usability, while augmented reality (AR)-enabled training and energy-efficient authentication protocols will address workforce and IIoT challenges. This study highlights the critical synergy between RBAC and HMI in smart manufacturing, proposing innovative solutions to bridge current gaps and drive next-generation industrial automation toward resilient, user-centric, and secure operations.
Keywords: Adaptive Interfaces; Human-Machine Interface (HMI); Industrial Cybersecurity; Industry 4.0; Role-Based Access Control (RBAC); multi-factor authentication (MFA); smart manufacturing